Determining tourism climate change mitigation and adaptation strategies at a selected private game reserve in South Africa - Sibitane, Zinzi Eugene (Vaal University of Technology, 2022)
Background Climate change is a significant threat that affects the natural environment and the industries dependent on it for their livelihoods, such as coastal and nature-based tourism. Regardless of this knowledge, vast knowledge gaps still exist regarding how climate variability and change affect nature tourism operations and response strategies. Aim This study aims to determine tourism climate change mitigation and adaptation strategies at one of the leading private game reserves in South Africa, Phinda Private Game Reserve. Methodology The study adopted the pragmatism philosophy, which informed the use of the mixed methods research design. Data collection was conducted at Phinda Private Game Reserve in May 2021. The data was collected through field observations, in-depth interviews with Phinda Private Game Reserve staff, archival and secondary data analysis. Primary data were analysed using qualitative data techniques, which followed an interactive content and thematic analysis process. Secondary data was analysed using content analysis, whereas trend analysis was applied to archival data (climate data). Using Mann Kendall Trend Analysis, trend analysis was analysed to track climatic trends such as climate variability and change and test their significance. Results and discussion The study identified several vital climatic challenges attributed to climate variability and change, increasing temperature, and extreme rainfall, resulting in localised flooding and droughts. These climatic threats have resulted in challenges for tourism operations ranging from disturbed sleep for tourism employees, dying off birds due to extreme heat, destruction of infrastructure, loss of biodiversity, water shortages and other such challenges over the last couple of years. The lodge has responded by adopting climate change mitigation adaption strategies to address carbon risk and extreme weather events. Measures adopted by the reserve include adopting measures aimed at reducing the company’s carbon footprint and protecting tourism infrastructure from the damaging impacts of extreme weather events. Recommendations The study recommends adopting additional measures to deal with its carbon footprint, such as investing in renewable energy as part of its mitigation strategy and continuing its research in biodiversity conservation, which can offer a solution to species protection in the context of climate change. The study also recommends continued research and monitoring of climate change impacts and tourism response, given the continued shift in the climate in the region.
MM (TTSM) (Department of Travel and Tourism Service Management, Faculty of Human Sciences), Vaal University of Technology.
Keywords: Climate change; Tourism; Mitigation; Adaptation; Game reserve; South Africa; Dissertations, Academic -- South Africa.; Tourism -- South Africa.; Climatic changes -- South Africa.; Environmental aspects -- South Africa.; Game reserves -- South Africa.; National parks and reserves -- South Africa -- KwaZulu-Natal.; Phinda Game Reserve (South Africa)